ACARORUM CATALOGUS X. Trombidiformes, Prostigmata, Superfamilia Labidostommatoidea (Labidostommatidae), Superfamilia Eupodoidea, (Eupodidae, Dendrochaetidae, Rhagidiidae, Eriorhynchidae, Pentapalpidae, Penthalodidae, Penthaleidae, Proterorhagiidae, Strandtmanniidae), Superfamilia Tydeoidea, Ereynetidae, Superfamily Paratydeoidea, Paratydeidae, Superfamilia Anystoidea, (Anystidae, Erythracaridae,Teneriffiidae, Pseudocheylidae, Stigmocheylidae), Superfamilia Caeculoidea (Caeculidae), Superfamilia Adamystoidea (Adamystidae), Superfamilia Pomerantzioidea (Pomerantziidae). - Beron, Petar (Pensoft Series Faunistica, 2022)
This is the last volume of the series Acarorum Catalogus. We tried to follow the system generally accepted. After the publication of the first volume of the series (Erytraeoidea, Calyptostomatoidea) in 2008 appeared a comprehensive treatment of mites (Manuel of Acarology III of Krantz & Walter, Eds. 2009), in which many changes in the system of Acari are proposed. Acariformes are already a superorder, Prostigmata - suborder, but within the order Trombidiformes. Here is treated first the infraorder Labidostommatina with its only superfamily Labidostommatoidea and the only family Labidostommatidae with five genera and 75 species. The other infraorder, treated in the present volume (Eupodoidea) includes the superfamily Eupodoidea with nine families, including five described after 1979. Treated are also the superfamilies Tydeoidea (fam. Ereynetidae), Paratydeoidea (Paratydeidae), Anystoidea (five families), Caeculoidea (Caeculidae), Adamystoidea (Adamystidae), and Pomerantzioidea (Pomerantziidae). In this volume are analysed 230 genera and 967 species of mites.